Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-32987-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of microbial dynamics in a drinking water distribution system using the culture-free, user-friendly, MYcrobiota platform

Abstract: Drinking water utilities currently rely on a range of microbiological detection techniques to evaluate the quality of their drinking water (DW). However, microbiota profiling using culture-free 16S rRNA gene next-generation sequencing (NGS) provides an opportunity for improved monitoring of the microbial ecology and quality of DW. Here, we evaluated the utility of a previously validated microbiota profiling platform (MYcrobiota) to investigate the microbial dynamics of a full-scale, non-chlorinated DW distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Unlike OTUs, ASVs can be resolved down to the level of single-nucleotide differences over the sequenced gene region that is expected to increase taxonomic resolution [ 104 ], although it could be argued that the fine-scale resolution obtained using ASV-based methods is actually not always desirable when processing highly complex samples. For example, the increased resolution of ASVs may increase the alpha diversity and reduce the overlap between samples, making downstream analyses more difficult compared to sequences that have been clustered into OTUs [ 105 ]. Further, OTU- and ASV-based methods will often produce comparable ecological results when the 16S rRNA gene is used as a genetic marker [ 106 ].…”
Section: Experimental Pitfalls and Biasesmentioning
confidence: 99%
“…Unlike OTUs, ASVs can be resolved down to the level of single-nucleotide differences over the sequenced gene region that is expected to increase taxonomic resolution [ 104 ], although it could be argued that the fine-scale resolution obtained using ASV-based methods is actually not always desirable when processing highly complex samples. For example, the increased resolution of ASVs may increase the alpha diversity and reduce the overlap between samples, making downstream analyses more difficult compared to sequences that have been clustered into OTUs [ 105 ]. Further, OTU- and ASV-based methods will often produce comparable ecological results when the 16S rRNA gene is used as a genetic marker [ 106 ].…”
Section: Experimental Pitfalls and Biasesmentioning
confidence: 99%
“…However, certain microbes, including opportunistic pathogens, survive disinfection and (re)grow in engineered water systems [EWSs, including DWDSs and building premise plumbing systems (PPSs)] (Hwang et al, 2012;Ashbolt, 2015a;El-Chakhtoura et al, 2018;Douterelo et al, 2019;Zhang and Liu, 2019;Zhang and Lu, 2021). Microorganisms in EWSs corrode iron and steel pipes (Ren et al, 2015;Xing et al, 2018;Zhu et al, 2019), deteriorate water taste and color (Zhou et al, 2017;Boers et al, 2018;El-Chakhtoura et al, 2018), and threaten public health [e.g., waterrelated disease outbreaks due to the (re)growth of opportunistic pathogens] (Ashbolt, 2015b;Liu et al, 2017;Wang et al, 2017;El-Chakhtoura et al, 2018;Chen et al, 2019;Zhang and Lu, 2021). Each year, more than one dozen drinking-water-related disease outbreaks occur in the United States (US), and opportunistic pathogen Legionella (mainly from EWSs) causes over 50% of these outbreaks (Beer et al, 2015;Benedict et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial biogeography has been documented in diverse aquatic ecosystems and on various spatial scales (Roeselers et al, 2015; Liu et al, 2018). Numerous studies revealed a remarkable heterogeneity (i.e., variations) in bacterial abundance (Liu et al, 2013; Siles and Margesin, 2016), metabolic activities (Chao et al, 2015; Charlop-Powers et al, 2015), or microbiomes (Stanish et al, 2016; Boers et al, 2018). Interestingly, this heterogeneity was not attributed to distance per se , but mainly to spatial differences in environmental factors (Hou et al, 2017; Langenheder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%